Why synchrony matters during mother-child interactions: a systematic review. - Chloë Leclère; Sylvie Viaux; Marie Avril; Catherine Achard; Mohamed Chetouani; Sylvain Missonnier; David Cohen (PLoS ONE)
Background Assessment of mother-child interactions is a core issue of early child development and psychopathology. This paper focuses on the concept of "synchrony" and examines (1) how synchrony in mother-child interaction is defined and operationalized; (2) the contribution that the concept of synchrony has brought to understanding the nature of mother-child interactions. Method Between 1977 and 2013, we searched several databases using the following key-words: "synchrony" "interaction" and "mother-child". We focused on studies examining parent-child interactions among children aged 2 months to 5 years. From the 63 relevant studies, we extracted study description variables (authors, year, design, number of subjects, age); assessment conditions and modalities; and main findings. Results The most common terms referring to synchrony were mutuality, reciprocity, rhythmicity, harmonious interaction, turn-taking and shared affect; all terms were used to characterize the mother-child dyad. As a consequence, we propose defining synchrony as a dynamic and reciprocal adaptation of the temporal structure of behaviors and shared affect between interactive partners. Three main types of assessment methods for studying synchrony emerged: (1) global interaction scales with dyadic items; (2) specific synchrony scales; and (3) micro-coded time-series analyses. It appears that synchrony should be regarded as a social signal per se as it has been shown to be valid in both normal and pathological populations. Better mother-child synchrony is associated with familiarity (vs. unknown partner), a healthy mother (vs. pathological mother), typical development (vs. psychopathological development), and a more positive child outcomes. Discussion Synchrony is a key feature of mother-infant interactions. Adopting an objective approach in studying synchrony is not a simple task given available assessment tools and due to its temporality and multimodal expression. We propose an integrative approach combining clinical observation and engineering techniques to improve the quality of synchrony analysis.